Immunophenotyping of acute lymphoblastic leukaemia in routinely processed bone marrow biopsy specimens. Issue 9 (1st September 1999) - Toth, B; Wehrmann, M; Kaiserling, E; Horny, H P
Abstract : AIMS: To assess the value of immunophenotyping of acute lymphoblastic leukaemia (ALL) in routinely processed bone marrow trephine biopsy specimens and to establish a minimum panel of antibodies to assess lymphoid lineage and enable differentiation from acute myeloid leukaemia. METHODS: 45 routinely processed bone marrow biopsy specimens (formalin fixed, paraffin embedded and mildly decalcified in EDTA) reported to contain leukaemic infiltrates on the basis of cytomorphological and enzyme-cytochemical analysis of bone marrow smears (22 c-ALL, 11 T-ALL, 2 B-ALL, 10 u-ALL (unclassified)) were immunostained by the ABC method with a broad panel of 26 antibodies against various haemopoietic antigens. RESULTS: Staining with antibodies directed against myeloperoxidase and lysozyme showed that seven cases were either biphenotypic or mixed leukaemias (2), or of myelogenous origin (acute myeloid leukaemia (AML)-M1 (2); AML-M4 (2); AML-M5a (1)). Five of these seven cases had been diagnosed initially as u-ALL. Three further cases with no compact leukaemic infiltrates were excluded. ALL was confirmed in the remaining 35 cases. Because of revised diagnoses, the total numbers of ALL subtypes changed (23 c-ALL, 8 T-ALL, 2 B-ALL, 2 u-ALL). Immunostaining of more than 10% of blast cells in at least one case was found with 19 of the 26 antibodies. The most sensitive lineage specific antibodies for diagnosis were found to be anti-CD10 for c-ALL (22/23) and beta F1 for T-ALL (6/8). Expression of aberrant antigens was fairly common–for example, 7/23 cases of c-ALL stained with antibodies against T cell associated antigens. CONCLUSIONS: Immunohistochemical investigation of routinely processed bone marrow biopsy specimens enables reliable detection of ALL subtypes c-ALL and T-ALL. A minimum panel of antibodies, against TdT, CD34, myeloperoxidase, lysozyme, CD10, CD79a, and CD20, and the antibody beta F1, is proposed for the immunophenotyping of acute leukaemia.